PENGUKURAN TINGKAT KAPABILITAS MANAJEMEN RISIKO SISTEM INFORMASI KOPERASI SYARIAH MENGGUNAKAN FRAMEWORK COBIT 5 - Ichwani, arief; Farida, Astrina Dewi (Universitas Lampung, 2020)
The application of IT offers many benefits in the company's business processes. Such as contribute to added value, excellent service, effective and efficient business operations. In addition to providing various benefits for business development, IT also has risk that must be managed optimally. This study aims to measure the level of risk management capabilities of the Syariah Cooperative Information System at KSPPS XYZ, the target level of capability and make a contribution to improvement. Measurement of the level of capability in risk management is done by using COBIT 5 domains EDM03 (Ensure Risk Optimisation) and APO12 (Manage Risk). Based on the measurements that have been made, domains EDM03 and APO12 capability levels are currently at level 0 (incomplete), while domains EDM03 and APO12 capability targets are level 3 (established). To achieve the capability level target, risk management approval is proposed for the KSPPS XYZ Syariah Cooperative Information System.Â